Preparation method of soil-dampening base temperature-sensitive composite gel blocking agent and application thereof
Patent Information
- Application Number
- CN202611093521.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-23
AI Technical Summary
[0008]本发明的目的在于克服现有技术中阻化剂持效性不足、单一功能明显、深部渗透与高温阶段抑制难以兼顾的问题,提出一种润土基温敏复合凝胶阻化剂制备方法
[0019]本发明所述一种润土基温敏复合凝胶阻化剂制备方法及其应用,其有益效果在于:本发明兼顾输送性和高温成胶性。利用温敏聚合物体系与PVA-硼砂交联体系的协同作用,使阻化剂在较低温度下保持较好的流动性,而在煤体温度升高后可快速形成三维网络结构,从而提高材料在高温敏感区域的滞留、覆盖和封堵能力;能延缓煤进入加速氧化区间,降低高温阶段深度氧化和热失稳;深部渗入和连续包覆性能好;具有矿物屏蔽、吸热和阻燃抑热复合效果;
Smart Images

Figure CN122958099A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of coal mine fire prevention and coal spontaneous combustion inhibition technology, specifically to a bentonite-based temperature-sensitive composite gel inhibitor formed by compounding bentonite, a high-molecular temperature-sensitive component and a flame-retardant component, and more specifically to a method for preparing the bentonite-based temperature-sensitive composite gel inhibitor and its application. Background Technology
[0002] During mining, transportation, storage, and the accumulation of residual coal in goaf areas, coal is prone to slow oxidation reactions with oxygen in the air. Although the initial reaction rate is low, it continuously releases heat. When the system's heat dissipation capacity is insufficient to balance this heat release, the coal temperature gradually rises, further accelerating the oxidation process and potentially inducing spontaneous combustion. Spontaneous combustion of coal not only results in the loss of coal resources but can also trigger secondary disasters such as fires, explosions, and the accumulation of toxic and harmful gases. Therefore, developing highly efficient fire-retardant materials that combine oxygen barrier, water retention, heat absorption, sealing, and flame retardant functions has always been an important research direction in the field of coal mine fire prevention and extinguishing.
[0003] Existing materials and methods for preventing spontaneous combustion of coal mainly include grouting, foaming, inert gases, inorganic salt inhibitors, composite colloids, and gel fire extinguishing materials. Among these, gel materials have attracted widespread attention due to their certain flow and diffusion properties, ability to fill cracks, and film-forming oxygen barrier effect. Patent CN101713296B proposes a composite gel inhibitor for preventing spontaneous combustion of coal in coal mines. It mainly involves graft copolymerization of a water-soluble polymer with an unsaturated carboxylic acid monomer, combined with a flame retardant and water glass to construct a composite system. This technology can achieve certain inhibitory and gelling effects, but its core technology leans towards the graft copolymer and water glass composite route.
[0004] Patent CN102173722A discloses a composite colloid for preventing spontaneous combustion of coal, with water glass, coagulant, aggregate, and water-retaining agent as the main components, emphasizing its leak-stopping, oxygen-barrier, and moisture-retaining effects. This type of technical solution leans more towards inorganic colloids and water-absorbing resin systems. Patent CN104083844B discloses a bentonite network gel foam mud fire extinguishing agent, which utilizes bentonite, sodium alginate, etc. to form a network foam mud film, focusing on spraying and surface covering for fire prevention and extinguishing. Patent CN103570375B discloses a foam gel preparation method, which expands the diffusion range by using foam as a carrier, focusing on solving the problems of foam collapse and gel solidification.
[0005] In recent years, thermosensitive gel materials have also been increasingly used in the prevention of spontaneous combustion of coal. Patent CN116041797A discloses a thermosensitive composite gel for preventing spontaneous combustion of coal in mines, which is prepared by combining thermosensitive polymer materials with organic and inorganic additives to create a composite gel capable of phase change sealing in high-temperature regions. Patent CN117625211A discloses a polymeric thermosensitive phase change gel material for inhibiting spontaneous combustion of coal, emphasizing that it changes from a liquid to a solid state and releases some moisture to achieve cooling after reaching the phase change temperature. Patent CN118304608B discloses a scheme for using inorganic thermosensitive phase change gel materials to prevent spontaneous combustion of coal, showing that this field is developing towards thermosensitive response and composite materials.
[0006] However, existing technologies still generally have the following shortcomings: While some inorganic colloids or water glass systems form gels quickly, they may exhibit high brittleness, poor water retention, and insufficient sustained chemical inhibition during on-site construction. Some foam gel systems are more suitable for surface covering or large-scale spraying, but still have limitations in deep fissure penetration and continuous coal particle coating. Although some polymeric thermosensitive systems possess temperature-responsive characteristics, the synergy between their flame retardancy, thermal inertization, and mineral shielding effects is limited. Existing technologies rarely organically integrate the adsorption-blocking characteristics of bentonite layered minerals, the cross-linking gelation characteristics of PVA-borax, the thermosensitive response characteristics obtained from NIPAM polymerization, and the synergistic flame retardant properties of APP / PER / ATH into a single system to address multiple requirements such as room-temperature transportability, rapid thickening and gelation upon heating, flame retardancy and oxygen suppression at high temperatures, and sustained water retention and thermal inertization.
[0007] Therefore, it is necessary to provide a new composite gel inhibitor and its preparation method, which has good fluidity and workability at room temperature or lower temperatures. When the coal temperature rises, it can rapidly thicken, gel, and coat the coal surface and pores through the combined action of temperature-sensitive polymer and cross-linked network. At the same time, it can achieve oxygen isolation, heat absorption, inhibition of deep oxidation, and increase the thermal runaway threshold by using bentonite, flame retardant and water retention system, thereby more effectively reducing the risk of coal spontaneous combustion. Summary of the Invention
[0008] The purpose of this invention is to overcome the problems of insufficient sustained efficacy, obvious single function, and difficulty in simultaneously addressing deep penetration and high-temperature stage inhibition in existing technologies. This invention proposes a method for preparing a clay-based temperature-sensitive composite gel inhibitor. This inhibitor exhibits good fluidity at lower temperatures, facilitating delivery and injection; at higher temperatures, it accelerates the formation of a three-dimensional network gel structure, enhancing its covering, encapsulation, and sealing effects on the coal surface and pores. Another objective of this invention is to propose the application of a clay-based temperature-sensitive composite gel inhibitor that, combined with the synergistic effect of flame-retardant and mineral components, reduces the oxygen reactivity of coal, inhibits oxygen consumption and exothermic processes, delays the transition of coal from low-temperature oxidation to accelerated oxidation, and improves the critical conditions for spontaneous combustion of the coal.
[0009] To achieve the above objectives, the present invention adopts the following technical solution: A bentonite-based thermosensitive composite gel inhibitor, wherein the components are formulated in the following mass ratios: 10-40 parts sodium bentonite, 10-30 parts polyvinyl alcohol, 5-20 parts N-isopropylacrylamide, 0.1-1 parts N,N′-methylenebisacrylamide, 0.2-1 parts ammonium persulfate, 30-70 parts ammonium polyphosphate, 3-10 parts pentaerythritol, 8-20 parts aluminum hydroxide, 1-5 parts citric acid, 3-10 parts borax, and appropriate amount of water; wherein, the N-isopropylacrylamide is polymerized in situ in the presence of polyvinyl alcohol and sodium bentonite to form a thermosensitive polymer, the ammonium polyphosphate, pentaerythritol, and aluminum hydroxide are dispersed in the system as flame retardant components, the citric acid is used to adjust the pH of the system before use to delay crosslinking, and the borax is added before use to initiate final crosslinking.
[0010] The present invention discloses a bentonite-based thermosensitive composite gel inhibitor comprising 25g sodium bentonite, 20g polyvinyl alcohol, 10g N-isopropylacrylamide, 0.25g N,N′-methylenebisacrylamide, 0.5g ammonium persulfate, 50g ammonium polyphosphate, 5g pentaerythritol, 11.75g aluminum hydroxide, 2.5g citric acid, 5g borax, and an appropriate amount of deionized water. The total amount of water used includes: 280g water for preparing the bentonite-based solution, 50g water for dispersing and dissolving polyvinyl alcohol, 20g water for dissolving ammonium persulfate, and an appropriate amount of deionized water for dissolving citric acid and borax.
[0011] The total amount of water used includes: approximately 280g of water for preparing bentonite-based solution, 50g of water for dispersing and dissolving polyvinyl alcohol, 20g of water for dissolving ammonium persulfate, and an appropriate amount of deionized water for dissolving citric acid and borax.
[0012] The bentonite-based system refers to a composite gel system composed of sodium bentonite (also known as bentonite) as the base mineral component, which, through the adsorption, filling, and shielding effects of its layered mineral structure, is combined with a polyvinyl alcohol-borax crosslinking network, a thermosensitive polymer formed by in-situ polymerization of N-isopropylacrylamide, and a flame-retardant component of ammonium polyphosphate / pentaerythritol / aluminum hydroxide.
[0013] The N-isopropylacrylamide is polymerized in situ in the presence of polyvinyl alcohol and bentonite to form a thermosensitive polymer. The ammonium polyphosphate, pentaerythritol and aluminum hydroxide are compounded and dispersed in the system as flame retardant components. The citric acid is used to adjust the pH of the system to delay crosslinking. The borax is used to initiate the final crosslinking before use.
[0014] The preparation method of the clay-based thermosensitive composite gel inhibitor of the present invention includes the following specific steps: Step S1, preparing bentonite-based liquid: Under stirring conditions, sodium-based bentonite is slowly added to water and stirred continuously to allow it to fully hydrate and swell, forming a uniform bentonite slurry; Step S2, preparing polyvinyl alcohol solution: After dispersing and swelling polyvinyl alcohol in water, stir at 90-95℃ until completely dissolved to obtain a transparent and viscous polyvinyl alcohol solution; Step S3, Mixing the base liquid and polyvinyl alcohol solution: Mix the bentonite base liquid obtained in step S1 with the polyvinyl alcohol solution cooled to below 40°C until homogeneous; Step S4, in-situ synthesis of thermosensitive polymer: N-isopropylacrylamide and N,N′-methylenebisacrylamide are added to the above mixture and stirred until dissolved. The system is then heated to 60-65°C, and ammonium persulfate initiator is added. The mixture is reacted at a constant temperature for 3-4 hours under nitrogen protection or in a closed environment to complete the polymerization and crosslinking reaction of N-isopropylacrylamide, and a premix containing polyvinyl alcohol and thermosensitive polymer is obtained. Step S5, add flame retardant components: Add ammonium polyphosphate, pentaerythritol and aluminum hydroxide to the premix obtained in step S4 in sequence, stir evenly, so that the flame retardant components are evenly dispersed in the system. Step S6, pH adjustment and final cross-linking: First, citric acid is added to the system to create an acidic environment, then borax solution is slowly added. Under low-speed stirring, the system undergoes further cross-linking to obtain a clay-based thermosensitive composite gel inhibitor. Borax solution is added before use to balance storage stability and on-site gelation.
[0015] The present invention relates to the application of a clay-based temperature-sensitive composite gel inhibitor in inhibiting low-temperature oxidation of coal and preventing spontaneous combustion of coal.
[0016] The inhibitor is used to reduce the oxygen consumption rate, heat release intensity, and CO and CO2 generation of the coal sample, and to increase the cross-point temperature and the coal spontaneous combustion tendency judgment index.
[0017] The bentonite-based system refers to a composite gel system composed of sodium bentonite (also known as bentonite) as the base mineral component, which, through the adsorption, filling, and shielding effects of its layered mineral structure, is combined with a polyvinyl alcohol-borax crosslinking network, a thermosensitive polymer formed by in-situ polymerization of N-isopropylacrylamide, and a flame-retardant component of ammonium polyphosphate / pentaerythritol / aluminum hydroxide.
[0018] This invention does not rely on a single water glass colloid system as its core, nor is it a simple foam slurry or a single temperature-sensitive phase change gel. Instead, it adopts a composite technical route of "bentonite + polyvinyl alcohol + temperature-sensitive polymer component + flame retardant component + delayed crosslinking", which is more conducive to taking into account the material's transportability, gelation properties and comprehensive inhibition capabilities.
[0019] The present invention discloses a method for preparing a clay-based thermosensitive composite gel inhibitor and its application. Its beneficial effects are as follows: the invention balances transportability and high-temperature gelation. Utilizing the synergistic effect of the thermosensitive polymer system and the PVA-borax crosslinking system, the inhibitor maintains good fluidity at lower temperatures, while rapidly forming a three-dimensional network structure after the coal temperature rises. This improves the material's retention, coverage, and sealing capabilities in high-temperature sensitive areas; it can delay coal from entering the accelerated oxidation zone, reducing deep oxidation and thermal instability at high temperatures; it has good deep penetration and continuous coating performance; and it possesses a composite effect of mineral shielding, heat absorption, and flame retardancy and heat suppression. The bentonite in this invention provides adsorption and shielding properties, the cross-linked structure formed by polyvinyl alcohol and borax helps construct a gel network, the thermosensitive component obtained by N-isopropylacrylamide polymerization helps improve the temperature response characteristics of the system, and ammonium polyphosphate, pentaerythritol, and aluminum hydroxide help enhance flame retardancy, heat absorption, and thermal inertization effects. Therefore, this invention exhibits good synergy in oxygen isolation, water retention, heat suppression, and chemical inhibition. Basic gel compositions, limited by their own material defects, cannot achieve the above transformations.
[0020] This invention adopts the method of "pre-mixed liquid + borax added before use for final cross-linking", which can take into account both storage and transportation stability and on-site construction window, and reduce the adverse effects of premature gelation on pumping and grouting. Attached Figure Description
[0021] Figure 1 This invention relates to the gel morphology and gelation process of the clay-based thermosensitive composite gel inhibitor. Figure 2 For the experimental procedure and apparatus; Figure 3 A comparison chart of temperatures at the intersection of different coal samples; Figure 4 This is a programmed temperature rise experimental system; Figure 5 The graph shows the variation of oxygen volume concentration with temperature for different coal samples. Figure 6 A graph showing the variation in oxygen consumption rate for different coal samples; Figure 7 Graphs showing the relationship between actual heat release intensity and temperature for different coal samples; Figure 8 This is a graph showing the variation of CO volume concentration in different coal samples. Figure 9 This is a graph showing the changes in CO2 volume concentration for different coal samples. Figure 10 A graph showing the variation of CO formation rate for different coal samples; Figure 11 This is a graph showing the variation in CO2 generation rate for different coal samples. Detailed Implementation
[0022] I. Experimental Materials and Instruments The bentonite-based thermosensitive composite gel inhibitor of this invention is based on a system of sodium-based bentonite, polyvinyl alcohol, and borax. At low temperatures, the polyvinyl alcohol molecular chains move freely, resulting in low slurry viscosity. At high temperatures, the molecular chain movement intensifies, accelerating the cross-linking reaction with borax and rapidly forming a three-dimensional network structure, thus achieving gelation. The main materials used in the experiment are shown in Table 1.
[0023] Table 1 Materials used in the experiment Na-based bentonite <![CDATA[AL2H2Na2O 13 Si4]]> Shanghai McLean Biochemical Technology Co., Ltd. Polyvinyl alcohol <![CDATA[(C2H4O)n]]> Shandong Keyuan Biochemical Co., Ltd. N-Isopropylacrylamide <![CDATA[C6H 11 NO]]> Shanghai McLean Biochemical Technology Co., Ltd. N,N'-methylenebisacrylamide <![CDATA[C7H 10 N2O2]]> Tianjin Huasheng Chemical Reagent Co., Ltd. ammonium persulfate <![CDATA[(NH4)2S2O8]]> Shanghai Ebi Chemical Reagent Co., Ltd. Borax decahydrate <![CDATA[Na2B4O7×10H2O]]> Shanghai Titan Technology Co., Ltd. Citric acid <![CDATA[C6H8O7]]> Guangdong Guanghua Technology Co., Ltd. Ammonium polyphosphate <![CDATA[(NH4)3PO4×3H20]]> Tianjin Damao Chemical Reagent Factory Pentaerythritol <![CDATA[C[CH2(OCH2CH2)nOH]4]]> Shanghai Aladdin Biochemical Technology Co., Ltd. Aluminum hydroxide <![CDATA[AL(OH)3]]> Shanghai McLean Biochemical Technology Co., Ltd. The specific experimental instruments used in the preparation process and effect verification method of the composite gel inhibitor are shown in Table 2.
[0024] Table 2. Instruments used in the experiment Magnetic stirrer JC-280H Shanghai Ronghui Instrument Technology Co., Ltd. Mechanical mixer NY-ES40 Jiangsu Enyi Instruments Co., Ltd. constant temperature water bath HH-1 Tianjin Sateri Laboratory Analytical Instruments Manufacturing Plant Gas chromatograph GC-6900 Shandong Guangrun Instrument Equipment Co., Ltd. Programmable heating chamber 101-5BD Changge Mingtu Machinery Equipment Co., Ltd. air compressor YY750-30L Zhejiang Shengyuan Air Compressor Manufacturing Co., Ltd. One-thousandth balance JA11003 Shanghai Platinum Temperature Instrument Co., Ltd. Example 1
[0025] The preparation method of the clay-based thermosensitive composite gel inhibitor of the present invention includes the following specific steps: Step 1: Preparation of base solution 1. Using a magnetic stirrer, add approximately 280g of water to a 500mL beaker, start stirring (200-300 rpm), but do not start the heating program; 2. Slowly add 25g of sodium-based bentonite and stir continuously for at least 60 minutes to allow it to fully hydrate and swell, forming a uniform bentonite slurry. Continue stirring until the slurry is transferred to a four-necked flask. Step 2: Dissolving Polyvinyl Alcohol (PVA) 1. In a 100mL beaker, disperse 20g of PVA powder (polyvinyl alcohol PVA-1788) with 50g of room temperature water and let it stand for 10 minutes to allow it to swell; 2. Then heat in a small water bath to 90-95℃, and use a mechanical stirrer to maintain a constant temperature and stir continuously for about 60 minutes (20-50 rpm, the speed should not be too high, just enough to show obvious signs of mixing from top to bottom), until the PVA is completely dissolved, and a transparent viscous solution, i.e., PVA solution, is obtained. Step 3: Mixing the base solution with the PVA solution 1. Pour the base solution prepared in step one into a 500mL four-necked flask; 2. Cool the PVA solution to below 40°C, then slowly pour it into the bentonite slurry and stir until homogeneous; Step 4: Synthesis of the temperature-sensitive polymer PNIPAM 1. Add 10g of NIPAM monomer (N-isopropylacrylamide) and 0.25g of crosslinking agent MBA (N,N′-methylenebisacrylamide) to the above mixture and stir at low speed until completely dissolved; 2. Raise the temperature of the four-necked flask to 60-65℃; 3. Dissolve 0.5g of initiator APS (ammonium persulfate) in 20g of water and add it quickly to the reactor in one go; 4. Under nitrogen protection (or in a closed environment), react at a constant temperature of 65℃ for 3-4 hours to complete the polymerization and crosslinking reaction of NIPAM; 5. After the reaction is complete, cool the system to room temperature to obtain a stable premix containing PVA and PNIPAM polymers; Step 5: Add flame retardant 1. Add 50g APP (ammonium polyphosphate), 5g PER (pentaerythritol), and 11.75g ATH (aluminum hydroxide) to the premixed solution in sequence. 2. Stir at high speed (500-600 rpm) for 60 minutes to ensure that all flame retardant powders are evenly dispersed and free of lumps; Step 6: Adjusting pH and final crosslinking 1. Dissolve 2.5g of citric acid in a small amount of water, add it to the system, and stir well (key step: add citric acid before borax to create an acidic environment and delay cross-linking). 2. Dissolve 5g of borax completely in hot water to make a borax aqueous solution; 3. Before use, slowly and uniformly add the borax solution to the slurry while stirring at low speed. Once borax is added, the cross-linking reaction begins, and the slurry viscosity will slowly increase. This step is best completed on-site at the pumping site, ensuring that the grouting is completed before the slurry viscosity reaches the pumping limit. See [link to gel morphology and gelation process] for details. Figure 1 . Example 2
[0026] Following the same preparation method as in Example 1, the components were prepared in the following proportions by weight: 12 parts sodium bentonite, 12 parts polyvinyl alcohol, 6 parts N-isopropylacrylamide, 0.15 parts N,N′-methylenebisacrylamide, 0.25 parts ammonium persulfate, 35 parts ammonium polyphosphate, 4 parts pentaerythritol, 9 parts aluminum hydroxide, 1.5 parts citric acid, 4 parts borax, and an appropriate amount of water. The remaining operations were the same as in Example 1. Example 3
[0027] Following the same preparation method as in Example 1, the components were prepared in the following proportions by weight: 18 parts sodium bentonite, 16 parts polyvinyl alcohol, 10 parts N-isopropylacrylamide, 0.3 parts N,N′-methylenebisacrylamide, 0.4 parts ammonium persulfate, 42 parts ammonium polyphosphate, 5 parts pentaerythritol, 12 parts aluminum hydroxide, 2.5 parts citric acid, 5 parts borax, and an appropriate amount of water. The remaining procedures were the same as in Example 1. Example 4
[0028] Following the same preparation method as in Example 1, the components were prepared in the following proportions by mass: 30 parts sodium bentonite, 25 parts polyvinyl alcohol, 15 parts N-isopropylacrylamide, 0.6 parts N,N′-methylenebisacrylamide, 0.7 parts ammonium persulfate, 55 parts ammonium polyphosphate, 7 parts pentaerythritol, 15 parts aluminum hydroxide, 3.5 parts citric acid, 7 parts borax, and an appropriate amount of water. The remaining procedures were the same as in Example 1. Example 5
[0029] Following the same preparation method as in Example 1, the components were proportioned in the following mass ratios: 38 parts sodium bentonite, 28 parts polyvinyl alcohol, 18 parts N-isopropylacrylamide, 0.9 parts N,N′-methylenebisacrylamide, 0.9 parts ammonium persulfate, 65 parts ammonium polyphosphate, 9 parts pentaerythritol, 18 parts aluminum hydroxide, 4.5 parts citric acid, 9 parts borax, and an appropriate amount of water. The remaining operations were the same as in Example 1.
[0030] Comparative Example 1 PVA+borax-based gel control group preparation steps To compare the technical effects of this invention, a polyvinyl alcohol + borax base gel was prepared as a control group. The specific steps are as follows: 1. Add 50g of deionized water and 20g of PVA to a 100mL beaker and disperse at room temperature for 10min; 2. Place the beaker in a 90–95℃ water bath and stir mechanically for 60 minutes until the PVA is completely dissolved, forming a transparent viscous solution; 3. Cool the PVA solution to below 40°C; 4. Take a small amount of deionized water and dissolve 2.5g of citric acid; 5. Take a small amount of hot water and dissolve 5g of borax to prepare a borax solution; 6. First, add the citric acid solution to the PVA solution and stir at low speed for 5 minutes; 7. Before use, slowly add the borax solution dropwise into the PVA system and stir for 10 minutes to obtain the PVA+borax base gel.
[0031] II. Coal Sample Preparation The coal sample used in this experiment came from Zuoyun Donggucheng Coal Industry Co., Ltd., a subsidiary of Shanxi Coal Import and Export Group. Its moisture content... M ad (%), Ash content A ad (%), volatile matter V ad (%), Fixed carbon content FC adThe percentages were 12.4%, 11.9%, 49.93%, and 25.77%, respectively. Large, fresh coal samples were placed in sealed bags and transported back to the laboratory. A liquid pressure press was used to crush the coal samples, which were then sieved to 18-35 mesh. The samples were then air-dried at 40℃ according to the GB 474-1996 method and used as the test samples. Four groups of 50g dried coal samples without any treatment were weighed and defined as raw coal. The remaining three groups of coal samples were treated with composite gels at ratios of 1:20, 1:10, and 1:5, respectively. PVA+borax-based gels were also used in the same manner as the experimental samples for programmed temperature rise. The specific processing methods and numbering of the coal samples are shown in Table 3.
[0032] Table 3 Coal Sample Processing Methods and Numbering - - RC Composite gel plus coal 1:20 5%NJ Composite gel plus coal 1:10 10%NJ Composite gel plus coal 1:5 20%NJ PVA + Borax base gel plus coal 1:20 5% PVA PVA + Borax base gel plus coal 1:10 10% PVA PVA + Borax base gel plus coal 1:5 20% PVA III. Experimental Procedure The experimental procedure was mainly based on the "Oxidation Kinetics Determination of Coal Spontaneous Combustion Tendency" (AQ / T 1068–2008). The ZRD coal spontaneous combustion characteristic testing device was used to program the temperature rise of the coal sample. The specific experimental procedure and device are as follows: Figure 2 As shown.
[0033] IV. Effects of different concentrations of clay-based thermosensitive composite gel inhibitors on the tendency of coal spontaneous combustion 1. Temperature variation pattern at the intersection point During programmed heating, the crossover temperature is one of the key thermodynamic parameters characterizing the spontaneous combustion tendency of different coal samples. This temperature is defined as the temperature corresponding to the first intersection of the coal sample temperature and ambient temperature curves. The lower the value, the lower the starting temperature at which significant low-temperature oxidation and self-heating effects occur, the stronger the spontaneous combustion tendency, and the easier it is for spontaneous combustion to occur. The temperature variation patterns of different coal samples are as follows: Figure 3 As shown.
[0034] from Figure 3It can be seen that at the very beginning of the experiment, the furnace temperature and the coal temperature are almost the same. As the furnace temperature continues to rise, the coal temperature also increases at an approximately constant rate, and its heating rate is lower than that of the furnace temperature. This is because as the coal temperature rises, the evaporation of moisture in the coal absorbs part of the heat, causing the coal temperature to deviate from the furnace temperature. However, as the reaction proceeds, coal oxidation releases heat, the coal temperature and the furnace temperature gradually approach each other, and become equal at a certain point in time. Eventually, the coal temperature exceeds the furnace temperature, and the heating rate increases significantly, entering a thermal runaway state. The cross-point temperature of the 5% NJ coal sample is 179.3°C. Compared with 170°C of the raw coal, the cross-point temperature of the coal sample added with 5% bentonite-based temperature-sensitive composite gel inhibitor is increased by 9.3°C. The cross-point temperature of the 10% NJ coal sample is 190.5°C, which is 20.5°C higher than that of the raw coal. The cross-point temperature of the 20% NJ coal sample is 205.1°C, which is 35.1°C higher than that of the raw coal. The effect of the composite gel inhibitor leads to a significant increase in the cross-point temperature of coal, and the cross-point temperature keeps rising as the proportion increases, making the coal sample less prone to spontaneous combustion.
[0035] At the same time, the comparison shows that although at low dosages of 5% and 10%, the PVA base gel has a cross-point temperature slightly higher than or equal to that of the composite gel group due to the initial film-forming coating effect of the simple polymer, in the key prevention and control stage of high dosage of 20%, the cross-point temperature (205.1°C) of the scheme of the present invention (20% NJ) is 16.3°C higher than that of the base gel group (20% PVA, 188.8°C). This strongly proves that the single PVA + borax base gel has a performance bottleneck at high concentrations caused by increased system brittleness and insufficient high-temperature sustainability. By introducing a multi-component synergistic system, this scheme breaks the performance upper limit of the prior art and exhibits stronger continuous inhibition capacity under high temperature and high dosage conditions.
[0036] 2. Spontaneous combustion propensity To further study the variation law of the spontaneous combustion propensity of coal samples treated with different concentrations of inhibitors, the influence of the inhibitor on the spontaneous combustion characteristics of coal can be judged by calculating the coal spontaneous combustion propensity index. The calculation formula is as follows:
[0037] In the formula:
[0038] In the classification of coal spontaneous combustion propensity, a judgment index I < 600 is classified as easy spontaneous combustion, 600 < I < 1200 as spontaneous combustion, and I > 1200 as non-spontaneous combustion. Combined Figure 3 with Formulas (2.1) to (2.3), the judgment index of coal spontaneous combustion propensity can be calculated, and the results are shown in Table 4.
[0039] It can be seen from Table 4 that the addition of the composite gel inhibitor significantly changes the key characterization parameters of the spontaneous combustion tendency of coal samples under programmed temperature rise conditions. The crossing point temperature of raw coal RC is 170℃, the corresponding outlet oxygen volume fraction is 19.04%, and the calculated crossing point temperature index and oxygen concentration index are 22.84 and 21.43 respectively, and the final spontaneous combustion tendency determination index I is 590.99, which is near the boundary of "easy spontaneous combustion" where I<600, indicating that RC can form a strong self-heating accumulation trend at the low-temperature oxidation stage; when the inhibitor dosage is 5% (5%NJ), the crossing point temperature rises to 179.3 ℃, the outlet oxygen concentration increases to 19.64%, and the corresponding crossing point temperature index and oxygen concentration index increase to 26.71 and 28.07, I increases to 790.18, falling into the "spontaneous combustion" grade interval (600<I<1200), which indicates that after the inhibition treatment, the critical temperature required for the furnace temperature-coal temperature crossing of the coal sample shifts upward, the heat release contribution of the low-temperature oxidation reaction is weakened, and the coal mass transforms from "easy self-heating" to "inhibited self-heating". Further increasing the dosage to 10% (10%NJ), the crossing point temperature continues to rise to 190.5℃, the outlet oxygen concentration is 19.85%, and the crossing point temperature index and oxygen concentration index reach 28.06 and 36.07 respectively, I rises to 950.69, indicating that the increase of inhibitor concentration not only raises the characteristic temperature at the onset of thermal runaway, but also shows a higher outlet oxygen concentration and a larger variation range of the oxygen concentration index at the 70℃ node, reflecting that the net oxygen consumption intensity of the coal sample decreases, and the coupling process of oxygen mass transfer and chemical adsorption / reaction is weakened. When the dosage increases to 20% (20%NJ), the crossing point temperature reaches 205.1℃, the outlet oxygen concentration significantly rises to 20.52%, and the crossing point temperature index and oxygen concentration index are 32.39 and 46.50 respectively, I increases to 1221.29 and crosses the 1200 threshold to enter the "not easy to spontaneously combust" interval, indicating that at this dosage, the inhibition of the composite gel system on the spontaneous combustion tendency of coal has developed from "delaying" to "significant passivation". Its macroscopic manifestations are, on the one hand, the continuous upward shift of the crossing point temperature means that the oxidative heat release per unit time is insufficient to offset the heat absorption of water evaporation and the heat dissipation of the system, and the thermal feedback is delayed; on the other hand, the outlet oxygen concentration increases with the increase of the dosage, indicating that the apparent oxygen consumption rate of the coal sample decreases, which may be related to the gel forming a continuous or semi-continuous covering layer on the surface of coal particles, filling the pores and increasing the tortuosity of the oxygen diffusion path, thereby reducing the effective diffusion flux of oxygen to the active sites. Meanwhile, the adsorption / shielding effect of the bentonite-based material and the water retention property of the gel jointly enhance the physical isolation and thermal inerting effects. On the whole, different coal samples show a monotonic increasing law of "crossing point temperature - index parameters - determination index" with the increase of inhibitor concentration, and IThe improvement from 590.99 to 1221.29 indicates that the composite gel inhibitor has a concentration-dependent synergistic regulatory effect on the kinetics of low-temperature oxidation reaction of coal and the conditions for thermal accumulation. It can effectively reduce the self-heating sensitivity of coal and increase the threshold for thermal runaway, thereby achieving graded reduction and controllability of spontaneous combustion risk at the macroscopic level.
[0040] Meanwhile, compared with the PVA+borax-based gel (PVA) control group, as the doping concentration increased from 5% to 10%, its I The value rose from 877.11 to 960.72, successfully entering the "spontaneous combustion" range; however, when the dosage increased to 20%, its... I The value also declined, dropping to 909.59. This indicates that no matter how the concentration of the basic gel system is increased, its inhibitory effect has a certain upper limit, and it can never cross the intrinsic safety threshold of 1200, remaining at the "spontaneous combustion" level. In the core scientific comparison with a high concentration of 20%, the judgment index (1221.29) of the present invention (20% NJ) is significantly improved by 311.7 compared with the closest prior art basic gel group (20% PVA, 909.59). More importantly, the present invention achieves a leap in the spontaneous combustion hazard level of coal samples from "spontaneous combustion" to "not easily spontaneously combustible," while the basic gel group, limited by its own material defects, cannot achieve this fundamental transformation.
[0041] Table 4. Characterization parameters of coal spontaneous combustion tendency
[0042] V. Effects of different concentrations of clay-based thermosensitive composite gel inhibitors on coal oxidation patterns 1. Coal sample processing The coal samples used in the experiment were crushed by applying pressure using a liquid pressure machine and then sieved to below 10 mm. Four groups of 200 g coal samples were weighed using a balance. The remaining three groups of coal samples were mixed with composite gels at ratios of 1:20, 1:10, and 1:5, respectively. The PVA+borax base gel was also used in the same manner as the experimental samples for programmed temperature rise.
[0043] 2. Experimental Procedure This programmed temperature rise experiment mainly consists of four systems: a programmed temperature rise system, a gas supply system, a temperature monitoring and acquisition system, and a gas sample acquisition and analysis system. The coal sample container used in the experiment is a copper container with an inner diameter of Ф=39mm, an outer diameter of Ф=42mm, and a height of H=270mm. A type K thermocouple was used to record the center temperature of the coal sample as the coal temperature. Heating was performed through a copper gas inlet pipe with an inner diameter of Ф=3mm, an outer diameter of Ф=4mm, and a length of L=50m. The experimental system is as follows: Figure 4 As shown.
[0044] 3. Oxygen Consumption and Heat Release Patterns The variation patterns of oxygen concentration in different coal samples are as follows: Figure 5 As shown, a lower oxygen concentration indicates a greater oxygen consumption during the low-temperature oxidation stage of coal, and a more vigorous oxidation reaction. From... Figure 4 As can be seen, the oxygen concentration of all coal samples exhibits a non-linear decreasing trend to varying degrees with increasing coal temperature. This directly reflects the kinetic characteristics of the coal-oxygen complex reaction's continuous consumption of ambient oxygen. The oxygen concentration curve of raw coal (RC) has the steepest downward slope, especially after crossing the endothermic stage of moisture evaporation and entering the accelerated oxidation period, where its oxygen consumption rate increases sharply. This indicates that the abundant active functional groups inside the raw coal undergo a violent exothermic reaction with oxygen, leading to a significantly enhanced heat accumulation effect.
[0045] Compared to raw coal, the oxygen concentration curve of coal samples treated with PVA+borax base gel shifted upwards overall, indicating that the base gel system could exert an inhibitory effect to some extent. This is mainly because the cross-linking of PVA and borax forms a certain gel network, which can construct a preliminary coating layer on the surface of coal particles, thereby hindering oxygen diffusion channels to some extent; at the same time, the water in the gel system evaporates and absorbs heat during heating, which weakens the exothermic reaction of coal oxidation to some extent. Therefore, the oxygen consumption of the PVA+borax base gel group is lower than that of raw coal. However, from Figure 5 It can be seen that although the oxygen concentration curve of the PVA+borax base gel group is higher than that of raw coal, its downward trend is still quite obvious. Especially after the temperature continues to rise, the outlet oxygen concentration still drops rapidly, indicating that the base gel system mainly relies on general gelling and water retention effects, and its ability to diffuse oxygen deep into the coal pores, shield active sites, and continuously inhibit oxidation at high temperatures is still limited.
[0046] In contrast, the oxygen concentration decrease in coal samples treated with bentonite-based composite gel inhibitors showed a significantly smoother trend and exhibited a marked concentration dependence. As the inhibitor dosage increased from 5% NJ to 10% NJ and then 20% NJ, the outlet oxygen concentration of the coal samples increased sequentially at the same temperature node, with the 20% NJ sample consistently maintaining the highest oxygen margin throughout the entire programmed temperature range. Particularly noteworthy is that, under the same addition ratio, the oxygen concentration curves of the bentonite-based composite gel group were consistently higher than those of the corresponding PVA+borax-based gel group. This indicates that the present invention does not merely utilize the conventional gelling effect of the PVA-borax system, but rather significantly enhances the inhibitory ability on the low-temperature oxidation process of coal through the combined effect of bentonite, temperature-sensitive polymer components, and flame-retardant components.
[0047] The reasons for these differences are as follows: While PVA+borax-based gels can form a certain three-dimensional network structure, their mechanism of action is mainly limited to surface coating and short-term water retention; whereas in bentonite-based composite gel inhibition systems, the layered mineral structure of bentonite can further enhance the adsorption, filling, and shielding capabilities on the coal surface, increase the tortuosity of oxygen molecule diffusion paths, and block some microporous channels; the temperature-sensitive polymer component can enhance the system's high-temperature viscosity and gel retention capacity under heating conditions, allowing the material to maintain good coverage and sealing effects even after the coal temperature rises; simultaneously, the synergistic effect of flame-retardant components and mineral components can also play a role in endothermic, thermal inertization, and inhibition of chain oxidation reactions during heating. In summary, Figure 5 This not only demonstrates that the clay-based composite gel inhibitor can significantly reduce the oxygen consumption intensity of coal samples during programmed heating, but also further illustrates that its inhibitory effect is significantly better than that of the PVA+borax-based gel control group, and can more effectively delay the development of coal from slow oxidation to accelerated oxidation.
[0048] The rate of oxygen consumption reflects the intensity of the coal spontaneous combustion reaction and is one of the important parameters characterizing the combustion process. Therefore, the oxygen consumption rate is also a major indicator for evaluating the probability of coal spontaneous combustion. Based on the differences in oxygen concentration under different conditions, the formula for calculating the actual oxygen consumption rate is shown in equation (2.4):
[0049] According to Equation 2.5, the oxygen consumption rate of coal samples treated with different concentrations of inhibitor can be calculated as follows: Figure 6 As shown in the figure, the oxygen consumption of all coal samples increases with increasing temperature. This indicates that the oxygen consumption rate of all coal samples gradually increases with temperature, but there are significant differences between different coal samples. In the coal temperature range of 30–100℃, the overall oxygen consumption rate of each coal sample is relatively low and the increase is relatively slow. At this time, the interaction between coal and oxygen is mainly physical adsorption and weak chemical adsorption, and the oxidation reaction activity of the coal body is still at a low level. Therefore, the differences between the curves are relatively small. As the temperature further increases, some active groups in the coal molecular structure gradually participate in the reaction, and the oxygen consumption rate of the coal samples begins to rise significantly. Raw coal (RC) consistently exhibits a high oxygen consumption rate throughout the heating process, especially after reaching 140℃, where its curve increases most rapidly. This indicates that the active sites on the surface and in the internal pores of raw coal are more likely to undergo continuous reactions with oxygen, resulting in a faster oxidation process and a more pronounced autothermal development trend.
[0050] Compared to raw coal, the oxygen consumption rate of coal samples treated with PVA+borax base gel decreased overall, indicating that the base gel system can inhibit the low-temperature oxidation process of coal to a certain extent. This is mainly because the gel network formed by the cross-linking of PVA and borax constitutes a preliminary covering layer on the surface of coal particles, increasing the resistance to oxygen diffusion. At the same time, the moisture retained by the gel absorbs heat through evaporation during the heating process, which weakens the thermal feedback of the coal oxidation reaction. Therefore, the oxygen consumption rate of the base gel group is lower than that of raw coal.
[0051] However, from Figure 6 Further analysis reveals that while the PVA+borax-based gel group shows some improvement compared to raw coal, its oxygen consumption rate still increases rapidly with rising temperature, especially exhibiting a significant upward trend in the medium- and high-temperature stages. This indicates that the basic gel system primarily functions as a general surface gel and provides short-term oxygen barrier, with limited ability to inhibit oxygen diffusion into the coal pores, weaken deep coal oxidation reactions, and delay the intensification of reactions at high temperatures. In contrast, the oxygen consumption rate of coal samples treated with the clay-based composite gel inhibitor is significantly lower overall, showing a regular decreasing trend with increasing inhibitor dosage. Specifically, the curves for 5% NJ, 10% NJ, and 20% NJ shift downwards sequentially, with 20% NJ maintaining the lowest oxygen consumption rate throughout the entire temperature-programmed range, indicating its most significant inhibition of coal oxidation. More importantly, at the same addition ratio, the oxygen consumption rate of the clay-based composite gel group is consistently lower than that of the corresponding PVA+borax-based gel group, demonstrating that this invention is superior to the basic gel system in reducing the coal oxygen reaction rate.
[0052] The essence of coal spontaneous combustion is the development of coal oxidation and heat dissipation. When the heat released during low-temperature coal oxidation exceeds the heat dissipated, heat accumulates in the coal pile, the temperature rises, and eventually spontaneous combustion occurs. Studying the exothermic intensity of coal is the only way to understand the coal spontaneous combustion process. The formula for calculating the exothermic rate is shown below:
[0053] Spontaneous combustion of coal is essentially the result of a competition between the heat released during coal oxidation and the heat dissipation of the system. When the rate of heat release during oxidation consistently exceeds the rate of heat dissipation, heat accumulates within the coal mass, eventually inducing spontaneous combustion. Therefore, analyzing the heat release intensity of coal samples during oxidation can further assess the development trend of spontaneous combustion. Based on the carbon and oxygen gas release rate and oxygen consumption rate of coal under specific conditions, the actual heat release intensity can be calculated as follows: Figure 7As shown in the figure, the exothermic intensity of each coal sample increases with increasing temperature, and exhibits a significant accelerated growth characteristic in the higher temperature range. Raw coal (RC) shows a high exothermic intensity throughout the entire experimental temperature range, and its exothermic curve rises most rapidly after entering the accelerated oxidation stage, indicating that raw coal has strong oxidation reactivity, fast heat release rate, significant self-heating accumulation effect, and is more likely to form thermal runaway conditions.
[0054] Compared to raw coal, the exothermic intensity of coal samples treated with PVA+borax base gel was reduced, indicating that the base gel system could weaken the low-temperature oxidation exothermic process of coal to some extent. This is mainly because the PVA-borax gel forms a certain physical coating layer on the surface of coal particles, slowing down the transfer of oxygen to reactive sites. At the same time, the evaporation of water in the system can absorb some heat, thereby weakening the accumulation of exothermic heat in the coal body to a certain extent.
[0055] However, although the exothermic intensity of the PVA+borax-based gel group was lower than that of raw coal, its curve still showed a relatively rapid upward trend in the medium and high temperature stages, indicating that its heat-suppressing effect was mainly concentrated in the lower temperature range. After the temperature continued to rise, the basic gel system was unable to continuously suppress the deep oxidation reaction and heat release of the coal body. In contrast, the exothermic intensity of the coal sample treated with the clay-based composite gel inhibitor was significantly lower, and the exothermic curve gradually shifted downward as the inhibitor concentration increased. Among them, the 20%NJ sample maintained the lowest exothermic intensity level throughout the entire heating process, indicating that its heat suppression effect was the most significant. Especially under the same dosage conditions, the exothermic intensity of the clay-based composite gel group was significantly lower than that of the corresponding PVA+borax-based gel group, indicating that the present invention has a superior technical effect compared to the basic gel system in suppressing oxidation exothermic reaction and delaying heat accumulation.
[0056] VI. The generation patterns of carbon and oxygen gases in coal oxidation and spontaneous combustion under treatment with different concentrations of clay-based thermosensitive composite gel inhibitors CO and CO2 are key gaseous products in the low-temperature oxidation process of coal. Their generation and release originate from both the physical adsorption and thermal desorption of CO and CO2 by the coal itself and are controlled by the kinetics of the oxidation reaction. Among them, CO is particularly typical, and its concentration change has significant stage characteristics, which can serve as an important indicative parameter for identifying different stages of coal oxidation (such as the latency period, accelerated oxidation period, and autothermal period).
[0057] The variation of CO volume concentration with temperature during programmed heating of different treated coal samples is as follows: Figure 7As shown in the figure, the CO concentration of all coal samples increased continuously with increasing temperature, but the different samples showed significant differences in the rate of increase and the temperature range of accelerated increase. Within the coal temperature range of 40-80℃, the CO volume concentration of each group of coal samples was generally low, and the curves were relatively similar, indicating that the coal-oxygen reaction was still in a weak stage at this time, and the CO change mainly came from the initial superposition of a small amount of adsorbed gas release and slow oxidation reaction. When the coal temperature rose to 80-120℃, the CO concentration of each coal sample began to gradually increase, indicating that the oxidation reaction gradually intensified. The raw coal (RC) curve first showed a significant steep increase near 120-140℃, and the subsequent increase was the largest, indicating that raw coal entered the accelerated oxidation range earliest, with more active groups in the coal molecules participating in the reaction, leading to rapid CO generation and accumulation.
[0058] Compared to raw coal, the overall CO volume concentration of coal samples treated with PVA+borax base gel was lower, indicating that the base gel system has a certain inhibitory effect on CO generation and release during low-temperature coal oxidation. This suggests that the capping layer and certain water retention effect formed by the base gel can, to some extent, delay oxygen entry into the coal body, reduce the oxidation reaction rate, and thus reduce CO generation. However, from... Figure 7 It can be seen that although the CO concentration curve of the basic gel group is lower than that of raw coal, it still rises rapidly with increasing temperature, especially showing a significant growth trend in the higher temperature range. This indicates that its inhibitory effect is more of a limited initial blocking effect, and its ability to control the rapid release of CO at high temperature is relatively insufficient.
[0059] In contrast, the CO concentration curves of coal samples treated with the clay-based composite gel inhibitor were significantly lower than those of raw coal and the PVA+borax-based gel group, and showed a gradual decrease with increasing inhibitor dosage. The CO concentrations of the 5% NJ, 10% NJ, and 20% NJ samples not only decreased sequentially, but the rapid CO growth range also shifted significantly later. The 20% NJ sample maintained the lowest CO volume concentration throughout the entire heating range, exhibiting the most significant inhibitory effect. Especially under the same addition ratio, the CO concentration of the clay-based composite gel group was lower than that of the corresponding PVA+borax-based gel group, indicating that this invention is significantly superior to the basic gel system in inhibiting CO generation and accumulation during coal oxidation.
[0060] This indicates that while PVA+borax-based gels can reduce some CO release through general gelling and covering effects, their strength and persistence are limited. In contrast, this invention, by introducing bentonite, temperature-sensitive polymerizing components, and flame-retardant synergistic components, enables the system to form a more stable and dense covering and sealing structure under heating conditions. This further weakens the coal oxidation reaction chain and the deep oxidation process at high temperatures, thereby more effectively reducing CO generation and delaying the emergence of its rapid growth temperature zone. In summary, Figure 7This indicates that the clay-based composite gel can not only significantly inhibit the release of CO during the low-temperature oxidation of coal, but its inhibition effect is also significantly better than that of the PVA+borax-based gel, demonstrating stronger sustained inhibition and high-temperature inhibition capabilities.
[0061] Figure 9 The figure illustrates the variation of CO2 volume concentration with temperature in coal samples under different treatments. Compared to CO, CO2 formation better reflects the deepening of coal oxidation; therefore, its trend is crucial for determining the transition from slow to deep oxidation. The figure shows that the CO2 concentration of each coal sample gradually increases with temperature, but the differences between samples are more pronounced at higher temperatures. In the 40-80℃ range, the CO2 concentration of each coal sample is relatively low and shows a slow upward trend. At this point, CO2 changes are influenced not only by the oxidation reaction but also by the desorption of pre-adsorbed gases and gas migration within the pores of the coal, resulting in relatively limited differences between samples. As the temperature further increases, the raw coal (RC) curve first diverges from other treatment groups, showing a significant accelerated upward trend after 120℃, with the steepest increase in the 130-150℃ range, ultimately reaching the highest concentration. This indicates that the deep oxidation reaction of raw coal is significantly enhanced in this temperature range, with the most intense CO2 generation and release.
[0062] Compared to raw coal, the overall CO2 volume concentration of the PVA+borax base gel group decreased, indicating that the base gel also has a certain weakening effect on the deep oxidation process of coal samples. This phenomenon suggests that the physical coating layer and water retention system formed by the base gel on the coal particle surface can slow down the oxygen mass transfer process to a certain extent and reduce some heat accumulation, thereby reducing CO2 generation. However, from... Figure 8 It can still be seen that the CO2 concentration of the PVA+borax-based gel group continues to rise rapidly in the medium and high temperature stages, especially in the high temperature zone, which shows a significant increase, indicating that its limiting effect on the later deep oxidation process of coal is still relatively limited.
[0063] In contrast, the CO2 concentration curve of the coal sample treated with the clay-based composite gel inhibitor was generally flatter, and the curve gradually shifted downward as the inhibitor concentration increased. The CO2 volume concentration of 5% NJ, 10% NJ, and 20% NJ decreased sequentially throughout the heating process, with 20% NJ consistently maintaining the lowest level and showing the slowest increase at high temperatures, indicating that it had the most significant inhibitory effect on the deep oxidation process of coal. In particular, at the same addition ratio, the CO2 concentration of the clay-based composite gel group was significantly lower than that of the corresponding PVA+borax basic gel group, which further demonstrates that the present invention has a superior incremental technical effect compared to the basic gel system in inhibiting deep oxidation at medium and high temperatures and reducing CO2 generation.
[0064] The CO generation rate is an important indicator for judging the degree of coal oxidation. Scholars believe that the CO generation rate indirectly reflects the types and quantities of functional groups involved in the oxidation-reaction process, and can also characterize the oxidation temperature of coal. The formulas for calculating the CO and CO2 generation rates at standard oxygen concentrations are shown in equations (2.8) and (2.9):
[0065] The CO generation rate of the coal sample can be calculated using Equation 2.8. Figure 10 As shown in the figure, the CO generation rate is a better indicator of the actual gas production intensity of a coal sample per unit time than the volume concentration, making it more representative for identifying the activity of the oxidation reaction and comparing the differences in reaction rates among different samples. The figure shows that when the coal temperature is between 40-90℃, the overall CO generation rate of each coal sample is relatively low and not significantly different, indicating that the coal samples are still mainly undergoing slow surface oxidation and low-level gas release, and the inhibitory effect of the inhibitor has not yet been fully utilized. As the temperature rises to 90-130℃, the CO generation rate of the RC sample begins to increase continuously and gradually widens the gap with the inhibited coal sample, indicating that the raw coal shows an enhanced oxidation reaction first. Above 130℃, the differentiation among the curves further widens, with the CO generation rate of the RC sample rising rapidly and the slope increasing significantly, indicating that the raw coal has entered a more active oxidation stage, and the CO gas production flux is rapidly amplified.
[0066] Compared to raw coal, the CO generation rate of the PVA+borax base gel group was generally lower, indicating that the base gel system inhibited the real-time CO generation during the low-temperature oxidation of coal to some extent. This suggests that the capping layer formed by the PVA-borax gel hinders the contact between the coal particle surface and oxygen, thereby reducing the oxidation reaction rate. As shown in the figure, the CO generation rate of the base gel group continued to increase significantly with further temperature rise, and there was still a large increase in the high-temperature region, indicating that its inhibitory effect on the CO generation flux during the high-temperature intensification stage was still limited.
[0067] In contrast, the CO generation rate of coal samples treated with the clay-based composite gel inhibitor was significantly lower, and the rate decreased sequentially with increasing inhibitor dosage. 5% NJ only showed a certain degree of attenuation, while 10% NJ and 20% NJ maintained low levels over a wide temperature range, with 20% NJ exhibiting the lowest CO generation rate throughout the entire heating process. More importantly, under the same addition ratio, the CO generation rate of the clay-based composite gel group was significantly lower than that of the corresponding PVA+borax-based gel group, indicating that this invention is superior to the basic gel system in reducing CO generation flux and slowing down the coal oxidation reaction.
[0068] The variation of CO2 generation rate with temperature in different coal samples is as follows: Figure 11As shown in the figure, within the temperature range of 40-110℃, the overall CO2 generation rate of each coal sample is relatively low, showing only a slight and slow increase. This indicates that the coal samples have not yet entered a strong deep oxidation stage, and the effect of the inhibitor on the rate differences between different samples is still relatively limited. After reaching 120℃, the RC curve first shows a significant inflection point, and then rises rapidly after 140℃, indicating that the oxidation degree of raw coal is significantly enhanced in this temperature range, and the reaction process is further transformed from slow oxidation to a higher intensity deep oxidation. Compared with raw coal, the CO2 generation rate of the coal sample treated with PVA+borax base gel is reduced, indicating that the base gel system has a certain weakening effect on the deep oxidation process of coal samples at high temperatures. This shows that the base gel can, to a certain extent, delay the diffusion of oxygen into the coal body and reduce the accumulation of some oxidation heat through water retention and heat absorption, thereby reducing the CO2 generation rate.
[0069] However, although the CO2 generation rate of the PVA+borax-based gel group was lower than that of raw coal, it still showed a significant increase at high temperatures, indicating that the basic gel system had limited control over the later stages of deep oxidation enhancement. In contrast, the CO2 generation rate inflection point of the sample treated with the binder-based composite gel inhibitor shifted significantly later, and the overall level was lower, with a significantly weaker peak growth rate. As the inhibitor dosage increased from 5% NJ to 10% NJ and then 20% NJ, the curve shifted downwards. Among them, 20% NJ maintained the lowest CO2 generation rate throughout the heating process, especially in the high-temperature region, indicating that it was most effective in inhibiting the later stages of deep oxidation of coal. Especially under the same dosage conditions, the CO2 generation rate of the binder-based composite gel group was consistently lower than that of the corresponding PVA+borax-based gel group, which clearly shows that the present invention is significantly superior to the basic gel system in limiting the flux of deep oxidation of coal samples at high temperatures.
[0070] The reason for this result is that the main function of PVA+borax-based gel is still conventional gel coating and a certain degree of water retention and oxygen barrier. However, this invention further introduces bentonite and a multifunctional synergistic system, enabling the material to not only possess stronger pore-filling and active site shielding capabilities, but also to continue exerting a sealing effect through temperature-sensitive thickening and high-temperature retention even after temperature increases. Simultaneously, the heat absorption and thermal inertization effects of the flame-retardant components weaken the oxidation process. Therefore, the bentonite-based composite gel can more significantly reduce the CO2 generation rate in the high-temperature zone, delaying the time when the coal sample enters the stage of severe deep oxidation. In summary, Figure 10 This further demonstrates that, compared to PVA+borax-based gel, the present invention has stronger and more lasting technical advantages in inhibiting deep oxidation of coal samples in the later stages and reducing the risk of thermal instability development.
[0071] VI. Conclusion This study systematically analyzed the inhibitory effect of a clay-based temperature-sensitive composite gel on coal spontaneous combustion using a programmed temperature rise experiment. The inhibitory effect was compared with that of a PVA+borax-based gel control group, leading to the following conclusions: (1) The clay-based thermosensitive composite gel inhibitor can significantly inhibit the low-temperature oxidation process of coal and have a significant impact on the spontaneous combustion tendency of coal. With the increase of the inhibitor dosage, the temperature at the cross point of the coal sample gradually increases, the spontaneous combustion tendency judgment index increases significantly, and the spontaneous combustion hazard level of the coal sample changes from "easy to spontaneously combustible" to "not easy to spontaneously combustible". This indicates that the composite gel inhibitor can effectively improve the critical conditions for spontaneous combustion of coal and reduce its risk of self-thermal instability.
[0072] (2) Compared with raw coal, PVA+borax-based gel has a certain inhibitory effect on the coal oxidation process, but its effect is mainly reflected in the initial gelation and short-term water retention and cooling. Compared with PVA+borax-based gel, the clay-based thermosensitive composite gel can maintain a higher outlet oxygen concentration and a lower oxygen consumption rate in the coal sample under the same dosage conditions, indicating that it has a stronger effect in hindering oxygen diffusion, weakening coal oxygen reaction and delaying oxidation development.
[0073] (3) The clay-based thermosensitive composite gel inhibitor can effectively reduce the actual exothermic intensity of coal samples during the heating process and significantly inhibit the generation amount and rate of CO and CO2. This inhibitory effect is more obvious in the medium and high temperature stages. The results show that the system can not only delay the transition of coal samples from slow oxidation to rapid oxidation, but also weaken the later deep oxidation process and reduce the accumulation rate of heat and characteristic gases.
[0074] (4) The reason why bentonite-based thermosensitive composite gel inhibitor is superior to PVA+borax-based gel is that it not only possesses the general gelling and coating effect of the PVA-borax system, but also combines the mineral adsorption and pore filling effect of bentonite, the thickening and blocking effect of the thermosensitive component under heating conditions, and the heat absorption and thermal inertization effect of the flame retardant component. Therefore, it exhibits better comprehensive effects in terms of oxygen isolation, heat suppression, water retention, and continuous inhibition. In summary, this inhibitor can effectively improve the thermal stability of coal and reduce the risk of spontaneous combustion of coal, and has certain engineering application value.
Claims
1. A clay-based thermosensitive composite gel inhibitor, characterized in that: The components are formulated in the following mass ratios: 10-40 parts sodium bentonite, 10-30 parts polyvinyl alcohol, 5-20 parts N-isopropylacrylamide, 0.1-1 parts N,N′-methylenebisacrylamide, 0.2-1 parts ammonium persulfate, 30-70 parts ammonium polyphosphate, 3-10 parts pentaerythritol, 8-20 parts aluminum hydroxide, 1-5 parts citric acid, 3-10 parts borax, and appropriate amount of water. The N-isopropylacrylamide is polymerized in situ in the presence of polyvinyl alcohol and sodium bentonite to form a thermosensitive polymer. The ammonium polyphosphate, pentaerythritol, and aluminum hydroxide are dispersed in the system as flame retardant components. The citric acid is used to adjust the pH of the system before use to delay crosslinking, and the borax is added before use to initiate final crosslinking.
2. The clay-based thermosensitive composite gel inhibitor as described in claim 1, characterized in that: The polyvinyl alcohol is PVA-1788; the water includes: water for preparing bentonite-based solution, water for dispersing and dissolving polyvinyl alcohol, water for dissolving ammonium persulfate, and water for dissolving citric acid and borax.
3. The clay-based thermosensitive composite gel inhibitor as described in claim 1, characterized in that, The solution comprises 25g sodium bentonite, 20g polyvinyl alcohol, 10g N-isopropylacrylamide, 0.25g N,N′-methylenebisacrylamide, 0.5g ammonium persulfate, 50g ammonium polyphosphate, 5g pentaerythritol, 11.75g aluminum hydroxide, 2.5g citric acid, 5g borax, and an appropriate amount of deionized water. The total amount of water used includes: 280g of water for preparing the bentonite-based solution, 50g of water for dispersing and dissolving polyvinyl alcohol, 20g of water for dissolving ammonium persulfate, and an appropriate amount of deionized water for dissolving citric acid and borax.
4. A method for preparing a clay-based thermosensitive composite gel inhibitor according to any one of claims 1 to 3, characterized in that, Includes the following steps: S1: Add sodium-based bentonite to water and stir to fully hydrate and swell it to obtain bentonite-based liquid; S2: After dispersing and swelling polyvinyl alcohol in water, stir at 90-95℃ until completely dissolved to obtain a polyvinyl alcohol solution; S3: Cool the polyvinyl alcohol solution obtained in step S2 to below 40°C and mix it evenly with the bentonite-based liquid obtained in step S1. S4: Add N-isopropylacrylamide and N,N′-methylenebisacrylamide to the mixture obtained in step S3, stir to dissolve, heat to 60-65°C, add ammonium persulfate, and react at a constant temperature for 3-4 hours under nitrogen protection or closed conditions to allow N-isopropylacrylamide to undergo in-situ polymerization and crosslinking reaction, and obtain a premix containing polyvinyl alcohol and temperature-sensitive polymer. S5: Add ammonium polyphosphate, pentaerythritol and aluminum hydroxide to the premix obtained in step S4 in sequence, stir evenly to make the flame retardant components evenly dispersed; S6: First, add citric acid to the system to adjust the pH. Before use, slowly add borax prepared as an aqueous solution. Under stirring conditions, the final cross-linking occurs to obtain the clay-based thermosensitive composite gel inhibitor.
5. The preparation method according to claim 4, characterized in that, In step S1, the stirring speed is 200-300 rpm, and the stirring time is at least 60 minutes.
6. The preparation method according to claim 4, characterized in that, In step S5, the stirring speed is 500-600 rpm and the stirring time is 60 minutes.
7. The preparation method according to claim 4, characterized in that, In step S6, the borax solution is added before use to ensure that cross-linking is completed during the pumping and infusion process.
8. The application of the clay-based thermosensitive composite gel inhibitor as described in any one of claims 1 to 3 in inhibiting spontaneous combustion of coal, characterized in that: The mass ratio of the inhibitor to the coal sample is 1:5 to 1:
20.
9. The application as described in claim 8, characterized in that, The inhibitor is fluid at room temperature to facilitate delivery and injection, and forms a three-dimensional network gel structure when the coal temperature rises, covering, encapsulating and sealing the coal surface and pores.
10. The application as described in claim 8, characterized in that, The inhibitor, through the synergistic effects of oxygen isolation, heat absorption, thermal inertization, and inhibition of coal oxygen reaction, delays the transition of coal from low-temperature oxidation to accelerated oxidation, thereby improving the critical conditions for spontaneous combustion of the coal.
Citation Information
Patent Citations
Composite gel inhibitor for preventing and controlling spontaneous combustion of coal in coal mine and preparation method thereof
CN101713296B
Composite gel for preventing spontaneous combustion of coal
CN102173722A
A method and apparatus for preparing foam gel for controlling spontaneous combustion of coal.
CN103570375B
Bentonite mesh gel foam mud fire extinguishing agent
CN104083844B
Temperature-sensitive composite gel for preventing and treating spontaneous combustion of mine coal and preparation method of temperature-sensitive composite gel
CN116041797A